2(c-7)+3(x-1)=4x+3

Simple and best practice solution for 2(c-7)+3(x-1)=4x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(c-7)+3(x-1)=4x+3 equation:


Simplifying
2(c + -7) + 3(x + -1) = 4x + 3

Reorder the terms:
2(-7 + c) + 3(x + -1) = 4x + 3
(-7 * 2 + c * 2) + 3(x + -1) = 4x + 3
(-14 + 2c) + 3(x + -1) = 4x + 3

Reorder the terms:
-14 + 2c + 3(-1 + x) = 4x + 3
-14 + 2c + (-1 * 3 + x * 3) = 4x + 3
-14 + 2c + (-3 + 3x) = 4x + 3

Reorder the terms:
-14 + -3 + 2c + 3x = 4x + 3

Combine like terms: -14 + -3 = -17
-17 + 2c + 3x = 4x + 3

Reorder the terms:
-17 + 2c + 3x = 3 + 4x

Solving
-17 + 2c + 3x = 3 + 4x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 2c + 17 + 3x = 3 + 17 + 4x

Reorder the terms:
-17 + 17 + 2c + 3x = 3 + 17 + 4x

Combine like terms: -17 + 17 = 0
0 + 2c + 3x = 3 + 17 + 4x
2c + 3x = 3 + 17 + 4x

Combine like terms: 3 + 17 = 20
2c + 3x = 20 + 4x

Add '-3x' to each side of the equation.
2c + 3x + -3x = 20 + 4x + -3x

Combine like terms: 3x + -3x = 0
2c + 0 = 20 + 4x + -3x
2c = 20 + 4x + -3x

Combine like terms: 4x + -3x = 1x
2c = 20 + 1x

Divide each side by '2'.
c = 10 + 0.5x

Simplifying
c = 10 + 0.5x

See similar equations:

| 16(x+3)=4(4x+1)+44 | | X+7+23x=23 | | -2x-4(-5x+18)=144 | | 1-(11x+3)=5 | | T(15-5t)=0 | | 0.5(x-3)=7 | | -8(t-2)-3(3t+1)=-4 | | 40*3= | | -25=4x+5 | | 19=-11+2x | | 2n+14-4n=26 | | 56x^2=79x-9 | | 3y+5=2x+1 | | 5x-3=3+2x | | 13-9x=-50 | | y+3=-11 | | 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 | | -2v(v-5)(v-6)=0 | | 7x(8-2)= | | 11k-5=9k+7 |

Equations solver categories